Implementasi Pembelajaran Role Playing Pada Pelajaran IPS Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD - Bella Alifia Aviari bella; Hadi Rohyana; Zubaidi (Jurnal Elementaria Edukasia, 2024)
Education is one of the crucial aspects in shaping character and enhancing the quality of human resources. Learning at the Elementary School (SD) level plays a strategic role in forming the foundation of knowledge and skills for students. To achieve these goals, innovative and effective learning models need to be introduced. One method that can be implemented is role-playing in Social Studies (IPS) learning for fourth-grade students. This research aims to improve students' learning outcomes in IPS through the implementation of the Role-Playing learning model for fourth-grade students. The analysis conducted on the implementation of Role-Playing in IPS is essential because through Role-Playing, students can directly portray what exists in their environment. Through IPS learning, students understand social climate, family, and environmental factors, shaping them into responsible and socially skilled citizens. The research method used is classroom action research with the spiral model by Kemmis and McTanggart, with 25 students from the fourth grade at SDIT Insan Teladan Mandiri as the research subjects. The research instruments include observation sheets, interviews, and worksheets for data collection. The data analysis involves qualitative descriptive analysis techniques that depict abilities or facts according to field conditions. Based on the research results, it is evident that the role-playing learning model is capable of enhancing students' learning outcomes in IPS for the fourth grade at SDIT Insan Teladan Mandiri.